Role of somatostatin in the prevention of pancreatic reactions in patients undergoing endoscopic retrograde cholangio-pancreatography (ERCP) - , Yusuf UZUN, Necati ÖRMECİ, Selim KARAYALÇIN, Cihan YURDAYDIN, Ali Reşit BEYLER, Özden UZUNALİMOĞLU, Abdülkadir DÖKMECİ (Turkish Journal of Gastroenterology 1, 2019)
-